Plate Tectonics - Frisch, Wolfgang; Meschede, Martin; Blakey, Ronald (Springer, 2011)
In the late 1960’s, Wegener’s theory of continental drift , originally conceived fi ft y years earlier, was merged with the theory of plate tectonics and the concepts gained global acceptance among geoscientists. For the fi rst time, a unifying concept, plate tectonics, could reconcile and unify all phenomena in geoscience into a common synthesis. Th e basic tenants have not changed since the 1960’s, although many corrections and refi nements have been added regarding questions of detail. Th e impact of the theory of plate tectonics cannot be overestimated – its importance to geoscience is as basic as Darwin’s theory of evolution is to the biological sciences. Earth is subject to steady change. Th is can impressively be realized in volcanic bursts and earthquakes around the Pacifi c Ocean or in the grandeur of young mountain ranges. Whilst new parts of plates are created along the mid-ocean ridges, older parts of plates disappear in subduction zones. Mountain chains arise from the collisions of plates. Th ese dynamic processes are driven by the heat that is released from the interior of the Earth; this is what keeps the dynamo running. Continental drift , mountain building, volcanism, earthquakes, and in consequence of quakes, sea waves like the devastating tsunami of 26th December 2004 in the Indian Ocean – all this is the expression of the dynamics of the Earth. Th is book presents an introduction in the wide fi eld of plate tectonics and is dedicated to a broad audience interested in natural sciences, and students and professionals in geosciences and related subjects. Expertise in tectonics is not a pre-condition; the technical terms and geological processes are explained and reviewed in adequate detail. Many terms are defi ned in the glossary at the end of the book and a keyword index enables quick location of topics and terms in the text. Figures at the inside front-end and back-end covers present concise overviews of the geologic timescale and critical events in Earth history as well as the classifi cation of magmatic and metamorphic rocks. More than 200 references enable the studious reader to gain deeper insight into special topics.
Continental D rift and Mountain Building